The mass of KOI-94d and a relation for planet radius, mass, and incident flux - Weiss, Lauren M.; Marcy, Geoffrey W.; Rowe, Jason F.; Howard, Andrew W.; Isaacson, Howard; Fortney, Jonathan J.; Miller, Neil; Demory, Brice-Olivier; Fischer, Debra A.; Adams, Elisabeth R.; Dupree, Andrea K.; Howell, Steve B.; et al. (The Astrophysical Journal, 2013)
We measure the mass of a modestly irradiated giant planet, KOI-94d. We wish to determine whether this planet, which is in a 22 day orbit and receives 2700 times as much incident flux as Jupiter, is as dense as Jupiter or rarefied like inflated hot Jupiters. KOI-94 also hosts at least three smaller transiting planets, all of which were detected by the Kepler mission. With 26 radial velocities of KOI-94 from the W. M. Keck Observatory and a simultaneous fit to the Kepler light curve, we measure the mass of the giant planet and determine that it is not inflated. Support for the planetary interpretation of the other three candidates comes from gravitational interactions through transit timing variations, the statistical robustness of multi-planet systems against false positives, and several lines of evidence that no other star resides within the photometric aperture. We report the properties of KOI-94b (M P = 10.5 ± 4.6 M ⊕, R P = 1.71 ± 0.16 R ⊕, P = 3.74 days), KOI-94c (M P = M ⊕, R P = 4.32 ± 0.41 R ⊕, P = 10.4 days), KOI-94d (M P = 106 ± 11 M ⊕, R P = 11.27 ± 1.06 R ⊕, P = 22.3 days), and KOI-94e (M P = M ⊕, R P = 6.56 ± 0.62 R ⊕, P = 54.3 days). The radial velocity analyses of KOI-94b and KOI-94e offer marginal (>2σ) mass detections, whereas the observations of KOI-94c offer only an upper limit to its mass. Using the KOI-94 system and other planets with published values for both mass and radius (138 exoplanets total, including 35 with M P < 150 M ⊕), we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to 13 Jupiter masses: (R P/R ⊕) = 1.78(M P/M ⊕)0.53(F/erg s–1 cm–2)–0.03 for M P < 150 M ⊕, and R P/R ⊕ = 2.45(M P/M ⊕)–0.039(F/erg s–1 cm–2)0.094 for M P > 150 M ⊕. These equations can be used to predict the radius or mass of a planet.
223 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-207-643-634-196, pop00005 tex.type: [object Object]
Keywords: dept.phy; planets and satellites: composition; techniques: photometric; techniques: spectroscopic

Kepler-15b: A hot jupiter enriched in heavy elements and the first kepler mission planet confirmed with the hobby-eberly telescope - Endl, Michael; Macqueen, Phillip J; Cochran, William D; Brugamyer, Erik; Buchhave, Lars A; Rowe, Jason F; Lucas, P W; Isaacson, Howard; Bryson, Steve; Howell, Steve B; Fortney, Jonathan J; Hansen, Terese; et al. (Astrophysical Journal Supplement Series, 2011)
We report the discovery of Kepler-15b (KOI-128), a new transiting exoplanet detected by NASA's Kepler mission. The transit signal with a period of 4.94days was detected in the quarter 1 (Q1) Kepler photometry. For the first time, we have used the High Resolution Spectrograph (HRS) at the Hobby-Eberly Telescope (HET) to determine the mass of a Kepler planet via precise radial velocity (RV) measurements. The 24 HET/HRS RVs and 6 additional measurements from the Fibre-fed chelle Spectrograph spectrograph at the Nordic Optical Telescope reveal a Doppler signal with the same period and phase as the transit ephemeris. We used one HET/HRS spectrum of Kepler-15 taken without the iodine cell to determine accurate stellar parameters. The host star is a metal-rich ([Fe/H]= 0.36 ± 0.07) G-type main-sequence star with Teff = 5515 ± 124 K. The semi-amplitude K of the RV orbit is 78.7+8.5 -9.5ms-1, which yields a planet mass of 0.66 ± 0.1 M Jup. The planet has a radius of 0.96 ± 0.06R Jup and a mean bulk density of 0.9 ± 0.2 gcm-3. The radius of Kepler-15b is smaller than the majority of transiting planets with similar mass and irradiation level. This suggests that the planet is more enriched in heavy elements than most other transiting giant planets. For Kepler-15b we estimate a heavy element mass of 30-40 M ⊕. © 2011. The American Astronomical Society. All rights reserved.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-839-775-387-264 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-15; KOI-128; KIC 11359879; 2MASS J19444814+4908244); techniques: image processing; techniques: photometric; techniques: radial Velocities; techniques: spectroscopic

A sub-Mercury-sized exoplanet. - Barclay, Thomas; Rowe, Jason; Lissauer, Jack; Huber, Daniel; Fressin, Francois; Howell, Steve; Bryson, Stephen; Chaplin, William; Desert, Jean-Michel; Lopez, Eric; Marcy, Geoffrey; Mullally, Fergal; et al. (Nature, 2013)
Since the discovery of the first exoplanets, it has been known that other planetary systems can look quite unlike our own. Until fairly recently, we have been able to probe only the upper range of the planet size distribution, and, since last year, to detect planets that are the size of Earth or somewhat smaller. Hitherto, no planets have been found that are smaller than those we see in the Solar System. Here we report a planet significantly smaller than Mercury. This tiny planet is the innermost of three that orbit the Sun-like host star, which we have designated Kepler-37. Owing to its extremely small size, similar to that of the Moon, and highly irradiated surface, the planet, Kepler-37b, is probably rocky with no atmosphere or water, similar to Mercury. © 2013 Macmillan Publishers Limited. All rights reserved.
161 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Earth; article; astronomy; atmosphere; dept.phy; irradiance; irradiation; moon; orbit determination; planetary surface; priority journal; size structure; solar system; sun; water

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-747-569-084-362 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b; KIC 10264660; 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Kepler-18b, c, and d: a system of three planets confirmed by transit timing variations, light curve validation, warm-spitzer photometry, and radial velocity measurements* - Cochran, William D.; Fabrycky, Daniel C.; Torres, Guillermo; Fressin, Francois; Désert, Jean-Michel; Ragozzine, Darin; Sasselov, Dimitar; Fortney, Jonathan J.; Rowe, Jason F.; Brugamyer, Erik; Bryson, Stephen T.; Carter, Joshua A.; et al. (Astrophysical Journal Supplement Series, 2011)
We report the detection of three transiting planets around a Sun-like star, which we designate Kepler-18. The transit signals were detected in photometric data from the Kepler satellite, and were confirmed to arise from planets using a combination of large transit-timing variations (TTVs), radial velocity variations, Warm-Spitzer observations, and statistical analysis of false-positive probabilities. The Kepler-18 star has a mass of 0.97 M ⊙, a radius of 1.1 R ⊙, an effective temperature of 5345K, and an iron abundance of [Fe/H] = +0.19. The planets have orbital periods of approximately 3.5, 7.6, and 14.9 days. The innermost planet "b" is a "super-Earth" with a mass of 6.9 ± 3.4 M ⊕, a radius of 2.00 ± 0.10 R ⊕, and a mean density of 4.9 ± 2.4gcm3. The two outer planets "c" and "d" are both low-density Neptune-mass planets. Kepler-18c has a mass of 17.3 ± 1.9 M ⊕, a radius of 5.49 ± 0.26 R ⊕, and a mean density of 0.59 0.07gcm 3, while Kepler-18d has a mass of 16.4 ± 1.4 M ⊕, a radius of 6.98 ± 0.33 R ⊕ and a mean density of 0.27 ± 0.03gcm3. Kepler-18c and Kepler-18d have orbital periods near a 2:1 mean-motion resonance, leading to large and readily detected TTVs. © 2011. The American Astronomical Society. All rights reserved.
144 citations (Crossref) [2023-10-31] Citation Key Alias: pop00006 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-18; KIC 8644288; 2MASS J19521906+4444467); techniques: photometric; techniques: spectroscopic

Kepler Planet-Detection Mission: Introduction and First Results. - Borucki, William; Koch, David; Basri, Gibor; Batalha, Natalie; Brown, Timothy; Caldwell, Douglas; Caldwell, John; Christensen-Dalsgaard, Jorgen; Cochran, William; DeVore, Edna; Dunham, Edward; Dupree, Andrea; et al. (Science, 2010)
The Kepler mission was designed to determine the frequency of Earth-sized planets in and near the habitable zone of Sun-like stars. The habitable zone is the region where planetary temperatures are suitable for water to exist on a planet's surface. During the first 6 weeks of observations, Kepler monitored 156,000 stars, and five new exoplanets with sizes between 0.37 and 1.6 Jupiter radii and orbital periods from 3.2 to 4.9 days were discovered. The density of the Neptune-sized Kepler-4b is similar to that of Neptune and GJ 436b, even though the irradiation level is 800,000 times higher. Kepler-7b is one of the lowest-density planets (∼0.17 gram per cubic centimeter) yet detected. Kepler-5b, -6b, and -8b confirm the existence of planets with densities lower than those predicted for gas giant planets.
2612 citations (Crossref) [2023-10-31] Place: Copyright (C) 2010 by the American Association for the Advancement of Science
Keywords: Jupiter; article; astronomy; astrophysics; density; dept.phy; gas; irradiation; planetary atmosphere; planetary surface; priority journal; spacecraft; sun; temperature; water

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
282 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
799 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
186 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22; KIC 10593626)